EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DENGAN IRINGAN MUSIK INSTRUMENTAL PADA MATERI GARIS DAN SUDUT DITINJAU DARI KEMAMPUAN HITUNG ALJABAR PESERTA DIDIK SMP NEGERI DI KABUPATEN MAGELANG TAHUN PELAJARAN 2012/2013 - Haryati, Ekaningsih; Mardiyana, Mardiyana; Sari, Dewi Retno (Jurnal Pembelajaran Matematika, 2013)
Abstract:The aims of the research were to determine the effect of learning models on learning achievement viewed from student’s algebra count ability. The learning models compared were cooperative learning (Numbered Heads Together (NHT) with instrumental musical accompaniment & NHT) and direct learning. The research typewasaquasi-experimental research.The research’s population wasthe 7th-grade students of the State Junior High Schools in Magelang Regency.It’s sampleswere takenby using stratified cluster random sampling techniquewhichconsisted of 97 students in the first experiment group, 99 students in the second experiment group, and 96 students in the control group.The datawas analyzed by using the unbalanced two-ways analysis of variance at the significance level of 0.05.The results of this research are as follows: (1) the both cooperative learningmodels result in the same goodlearning achievement, but its resultin a better learning achievement than the direct learning model; (2) the learning achievement of the students with the high level of algebra count ability is better than that of those with the medium and the low levels of it, the learning achievement of the students with the medium level of algebra count ability is better than that of those with the low level of it; (3) in each levelsof algebra count ability shows thatthe both cooperative learningmodels result in the same good learning achievement, but its result in a better learning achievement than the direct learning model; (4) in each learning model shows that the learning achievement of the students with the high level of algebra count ability is better than that of those with the medium and the low levels of it, the learning achievement of the students with the medium level of algebra count ability is better than that of those with the low levelof it. Keywords: NHT,instrumental music, algebra count ability, learning achievement.